LINGUISTIC FEATURES ANALYSIS OF THE ENGLISH ELECTRONIC COMMERCE WEBSITES - Siti Nurani; Risa Mufliharsi; Larisa Yohanna (University of Kuningan, 2014)
Abstract:Â This research aims at identifying linguistic features used in the English electronic commerce websites used in correlation with the field, tenor and mode of discourse as parts of Systemic Functional Linguistics (SFL) approach. Findings have shown that in the field of discourse, the linguistic features are largely appeared in the experiential domain analysis which shows that all terms of registers function as technical terms, of which the two major forms of nouns and verbs were the most frequent categories among other kinds of technical terms. The goal orientation is considered to be as a long term and the social activity is exchange. In the tenor of discourse, the linguistic features are highly appeared in the social distance analysis which shows that the social distance between participants is considered minimal. The agentive role is said to be equal and the social role is considered as non-hierarchic. In the mode of discourse, the linguistic features are excessively occurred in the language role analysis which exists equally of both constitutive and ancillary. The channel is in graphic mode. The medium is in written with a visual contact as its device.Key words: systemic functional linguistics, register, discourse